Online Learning and Students’ Fear of COVID-19: Study in Malaysia and Pakistan - Munir, Farhat; Anwar, Aizza; Kee, Daisy Mui Hung (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
The COVID-19 pandemic has forced millions of students to stay indoors and adapt to the new normal, namely distance learning at home, placing online learning in the spotlight. However, students’ motivation for online learning and its effectiveness in skill development during the COVID-19 pandemic has not been widely studied. This study examined the relationship between students’ fear of COVID-19 and students’ social presence in online learning while investigating the parallel mediating role of student psychological motivation and cognitive problem-solving skills related to online learning. The participants were 472 university students in Malaysia and Pakistan. An online data collection technique using Google Forms was employed. Faculty members of the universities were asked to share the survey with their students. Moreover, using a snowball sampling technique, students were requested to share the survey with their friends. SPSS Statistics (Version 21)  was employed to do preliminary data analysis, AMOS (Version 21) software was used to conduct confirmatory factor analysis using a maximum likelihood estimation, and Hayes’ PROCESS model was used to examine proposed hypotheses. The results show that only cognitive problem solving mediates the relationship between fear of COVID-19 and students’ social presence in online learning in Malaysian samples. In Pakistan, cognitive problem solving and psychological motivation mediate the relationship between fear of COVID-19 and students’ social presence in online learning. The study found that developing cognitive problem-solving skills and providing psychological motivation could enhance their engagement with online learning.